Site and Re-Site: Early Efforts to Serialize Site Dance. Issue 1 (19th April 2017) - Kloetzel, Melanie
Abstract : In this article, I investigate the historical precedents of site-adaptive dance. After walking through the mobility discourse as applied to site-specific art by such scholars as Miwon Kwon, Fiona Wilkie, and Victoria Hunter, I examine the mobile site works of North American choreographers Ann Carlson, PearsonWidrig DanceTheater, Eiko & Koma, and Stephan Koplowitz as exemplary of early attempts to take site dance on tour. Finally, I argue for the value of employing the lens of adaptation to analyze such works, both for the field of site performance and for the larger cross-disciplinary dialogues that could be activated.